The Utilization of Punan River Water for Communities Around the Mine, Gunung Tabur District, Berau Regency, East Kalimantan - Sugiarto, Wahyu; Retno Astuti, Theophila Listiyani (ReTII, 2023)
Berau Regency is one of the areas with Mining Business Permit Areas so it can affect river water quality. Water is a natural resource that is necessary for the livelihoods of many people and even all living creatures. River water is very useful, especially for people in residential areas. The role of rivers is to provide a source of life for humans, such as the use of water and the fertility of the surrounding land. The aim of this research is to determine the physical, chemical and microbiological parameter values of the Punan River intake water, clean water (Water Treatment Plant) and drinking water (Reverse Osmosis) at the research location. The research method used was sampling the Punan River intake water, clean water for sanitation hygiene purposes (Water Treatment Plant) and drinking water (Reverse Osmosis). The average pH value of the Punan River intake water is 7.8 and clean water is 7.5 and drinking water is 7.1. The average turbidity of clean water is 14 NTU and drinking water is <0.01 NTU. All physical, chemical and biological parameters in the Punan River intake water, clean water and drinking water are at the required quality standard values. The Water Treatment Plant and Reverse Osmosis processes can eliminate Coliform and E.Coli bacteria.